Expression and Purification of Recombinant Pneumococcal Surface Proteins from E.coli - Bansal, Tamanna (My University, 2019)
Streptococcus pneumoniae is a gram-positive bacterium that causes invasive disease like pneumonia in lungs, bacteraemia in blood and meningitis in the central nervous system. Youngest and oldest segments mostly get affected by the disease in both developed and developing nations. The worldwide presence of pneumococcal resistance to antibiotics like penicillin complicates the therapy of pneumococcal infection. There are two vaccines available to address the worldwide pneumococcal disease burden, the 13-valent conjugate vaccine and the 23-valent non-conjugated polysaccharide-based vaccine. However, these two vaccines have limitations due to their capsular serotype- specific composition. Therefore, they elicit only serotype-specific immunity. As pneumococci can express diversified pool of capsular polysaccharide serotype, research is now centred on discovering more conserved protein- based antigen that could provide better defence against pneumococci. Present study focuses on exploring potential pneumococcal protein antigens as vaccine candidates. Pneumococcal surface adhesin A and SP0845 were the focus of this study.
M.Sc. thesis
Keywords: Streptococcus pneumoniae; Pneumococcal vaccines; Protein based vaccines; PsaA; SP0845